Pengaruh Content Marketing Dan Perceived Ease of Use Terhadap Kepuasan Penggunaan Aplikasi BYOND Pada Nasabah Bank Syariah Indonesia - Dinda Najwa Legina; Rita Kusumadewi; Toto Suharto (Fakultas Ekonomi dan Bisni Islam UIN Siber Syekh Nurjati Cirebon, 2026)
This study examines the influence of content marketing and perceived ease of use on user satisfaction with the BSI Mobile app among Bank Syariah Indonesia customers at the BSI Kuningan Branch, using a quantitative method through a survey of 100 respondents selected via purposive sampling. Primary and secondary data were analyzed using SmartPLS 4 through outer model analysis, inner model analysis, and hypothesis testing. The results of the study indicate that, individually, content marketing (F² = 0.112) and perceived ease of use (F² = 0.881) have a positive and significant effect on user satisfaction; simultaneously, these two variables also have a positive and significant effect with an R² value of 0.772, or 77.2%, indicating a strong contribution to increasing user satisfaction with the BSI Mobile app.